Covid-19 and Capital Flows: The Responses of Investors to the Responses of Governments - Stefan Goldbach; Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper examines the effect of national government response measures to Covid-19 on German international capital flows. Analyzing highly disaggregated monthly data from the German balance of payments statistics over the period from January 2019 through January 2021, we find that bilateral financial interactions are negatively affected by stricter containment and closure policies as well as health system policies of a partner country, while German capital flows benefit from a partner's economic support policies. Moreover, to the extent that public interventions to fight the pandemic affect financial interactions, the adjustment mainly takes place along the intensive margin.
Keywords: F36; F60; I18; 330; coronavirus; pandemic